"The Politics of the HealthCare Reform Debate: Public Support of Including Undocumented Immigrants and Their Children in Reform Efforts in the U.S.". Issue 2 (June 2013) - Sanchez, Gabriel R.; Sanchez-Youngman, Shannon
Although U.S. immigration and health care policies appear to be highly correlated, scholarship has yet to gauge the public's views toward providing undocumented immigrants with health coverage at the state level. We analyze support for including undocumented immigrants in health care reform in New Mexico. Utilizing an original public opinion survey of New Mexico adults, we find that individuals are more supportive of the state providing health care to the children of undocumented immigrant than to their parents. Multivariate logistic regression analyses suggest that factors such as liberal ideology and perceptions of commonalities with Latinos increase support levels. Despite a lack of support among a majority of respondents, the influence of perceived commonalities with immigrants suggests that reform advocates and political elites who mobilize along ethnic or human solidarity may be successful in creating conditions for the inclusion of undocumented immigrants in the public provision of health care at the state level.